If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying cosx + 2 = 1 + -1cosx Reorder the terms: 2 + cosx = 1 + -1cosx Solving 2 + cosx = 1 + -1cosx Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add 'cosx' to each side of the equation. 2 + cosx + cosx = 1 + -1cosx + cosx Combine like terms: cosx + cosx = 2cosx 2 + 2cosx = 1 + -1cosx + cosx Combine like terms: -1cosx + cosx = 0 2 + 2cosx = 1 + 0 2 + 2cosx = 1 Add '-2' to each side of the equation. 2 + -2 + 2cosx = 1 + -2 Combine like terms: 2 + -2 = 0 0 + 2cosx = 1 + -2 2cosx = 1 + -2 Combine like terms: 1 + -2 = -1 2cosx = -1 Divide each side by '2osx'. c = -0.5o-1s-1x-1 Simplifying c = -0.5o-1s-1x-1
| n^2=-25-12n | | -9x-5=6x+40 | | Y^2*DX+(3XY-4Y^2)DY=0 | | 9s=45 | | Y^2DX+(3XY-4Y^2)DY=0 | | -3(6x+6)=90 | | 5*x-16=52 | | 3y+11=38 | | 117-81=35y-44y | | z^2+(2+2i)z+6i=0 | | 9p^2+12pq+4q^2=0 | | 9y+5=165 | | 2-b=15 | | 2(3x-5)=6(2x+4) | | y=5x-2forx | | -7+3+3x=-38 | | [2(y+5)]=40 | | -6x+8x-7=2(x-2)-5 | | -4w+5+5w=2-1 | | -93=3(-4b-7) | | (3x+2)(3x+2)(3x+2)= | | 56=(.5x)(2x+2) | | 5-3=5*3 | | -25+12=m-6 | | 9x^7-100x^3=0 | | 2w+9-5w=4+3w-7 | | 2(2n+4)=9(3n+6)8 | | 8=-1233 | | 4w+5+5w=2-1 | | -(5+3r)=2r-20 | | 9x-5=274 | | 9y+5=130 |